A comparative evalaution on the performance and emission characteristics of an internal combustion engine using ceramic and metallic catalytic converter - Jajuli, Fatin Afiqah (2017)
Automobile exhaust emission control is one of trending issues in automotive research field. Ceramic and metallic catalytic converters are the most common types of catalytic converters. Most current researches focus on the modeling and characterization of catalytic converter and there is a lack of exhaust gas conversion data of different catalyst types that correspond to real engine operating condition. This project focuses on comparing and analyzing the perfonnance of ceramic and metallic catalytic converter on its conversion efficiency. Mitsubishi 4G93 1800cc gasoline engine was attached with a dynamometer and Kane Auto 5-1 series exhaust gas analyzer were used for emission measurements of carbon monoxide (CO), hydrocarbon (HC) and nitrogen oxide (NOx) in different speed and constant load. The experimental results of the engine performance and exhaust emission were used to compare the perfonnance of ceramic and metallic catalytic converters in reducing the concentration of the exhaust emission without affecting the engine perfonnance. Based on the result, metallic catalytic converter showed a higher 97.9% reduction of CO concentration reduction emission as compared to the ceramic catalytic converter. The ceramic catalytic converters on the other hands showed better reduction ofNOx and HC concentration of 87.2% and 85.4% percentage of reduction. It can be concluded that metallic catalytic converters performs a better exhaust gas conversion on high temperature condition at reducing CO emission while ceramic catalytic converters reduced HC and NOx emission more effectively due to its lower thermal conductivity